Fully automated myocardial strain estimation from cine MRI using convolutional neural networks - Puyol-Anton, Esther; Ruijsink, Bram; Bai, Wenjia; Langet, Helene; De Craene, Mathieu; Schnabel, Julia A.; Piro, Paolo; King, Andrew P.; Sinclair, Matthew (Proceedings - International Symposium on Biomedical Imaging, 2018)
Cardiovascular magnetic resonance myocardial feature tracking (CMR-FT) is a promising method for quantification of cardiac function from standard steady-state free precession (SSFP) images. However, currently available techniques require operator dependent and time-consuming manual intervention, limiting reproducibility and clinical use. In this paper, we propose a fully automated pipeline to compute left ventricular (LV) longitudinal and radial strain from 2- and 4-chamber cine acquisitions, and LV circumferential and radial strain from the short-axis imaging. The method employs a convolutional neural network to automatically segment the myocardium, followed by feature tracking and strain estimation. Experiments are performed using 40 healthy volunteers and 40 ischemic patients from the UK Biobank dataset. Results show that our method obtained strain values that were in excellent agreement with the commercially available clinical CMR-FT software CVI42 (Circle Cardiovascular Imaging, Calgary, Canada).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Automatic pipeline; Machine learning; MRI; Myocardial Strain